Impact of paternity leave on maternal postpartum recovery and mental health: policy frameworks in India and Kerala - Amaya Prakash; Sithara Balan Vijayakumari (International Journal Of Community Medicine And Public Health, 2026)
The recognition of paternity leaves as a key element in supporting maternal recovery and improving postnatal care quality is increasing. Although there is increasing global evidence highlighting its advantages, the implementation and effects of paternity leave policies differ widely, with India exemplifying this variation. This review aimed to gather and analyse current evidence on how paternity leave influences maternal physical and mental health during the postpartum period, with a particular focus on the policy frameworks and practices in India and Kerala. An extensive search was carried out across several databases, such as PubMed, Scopus, web of science, and google scholar, to locate pertinent studies published between 2004 and 2025. The search utilized keywords associated with “paternity leave,” “postnatal care,” “maternal recovery” and “parental leave policies.” Official documents, policy papers, and government notifications from India and international organizations were examined to understand the legislative and policy contexts. Paternity leave is increasingly viewed as a public health measure aiding maternal recovery. Fathers’ involvement during this time helps alleviate physical strain, musculoskeletal stress, and fatigue. Additionally, it acts as a safeguard against postpartum depression and stress in mothers. Yet, policy implementation varies widely. In India, Central Government employees are entitled to 15 days of paid leave, while Kerala State Government employees receive 10 days. In contrast, the private sector lacks a uniform statutory provision, resulting in considerable disparities in family support. Ensuring statutory, paid, and job-protected paternity leave of adequate length is crucial for enhancing health outcomes for both mothers and infants.